Influence of Salmonella enterica serovar Enteritidis infection on the composition of chicken cecal microbiota - Videnska, Petra; Sisak, Frantisek; Havlickova, Hana; Faldynova, Marcela; Rychlik, Ivan (BMC veterinary research, 2013)
BACKGROUND: Infection of newly hatched chicks with Salmonella enterica serovar Enteritidis (S. Enteritidis) results in an inflammatory response in the intestinal tract which may influence the composition of gut microbiota. In this study we were therefore interested whether S. Enteritidis induced inflammation results in changes in the cecal microbiota. To reach this aim, we compared the cecal microbiota of non-infected chickens and those infected by S. Enteritidis by pyrosequencing the V3/V4 variable regions of genes coding for 16S rRNA. RESULTS: Cecal microbiota of chickens up to 19 days of life was dominated by representatives of Enterobacteriaceae, Lachnospiraceae and Ruminococcaceae, followed by Lactobacillaceae. The presence of Lachnospiraceae did not change after S. Enteritidis infection. Enterobacteriaceae increased and Ruminococcaceae decreased after S. Enteritidis infection in two independent experiments although these results were not significant. A significant increase in both experiments was observed only for the representatives of Lactobacillaceae which may correlate with their microaerophilic growth characteristic compared to the obligate anaerobes from the families Lachnospiraceae and Ruminococcaceae. CONCLUSIONS: We conclude that S. Enteritidis infection influences the composition of the cecal microbiota in chickens but these changes are minor in nature and should be understood more as an indirect consequence of infection and inflammation rather than a positively selected evolutionary trait.
Keywords: kur domácí; Poultry Diseases; Male; kvantitativní polymerázová řetězová reakce; Chickens; RNA, Ribosomal, 16S; mikrobiota; Lactobacillus; cékum; mužské pohlaví; Microbiota; Real-Time Polymerase Chain Reaction; Cecum; salmonelová infekce u zvířat; nemoci drůbeže; Salmonella Infections, Animal; Animals; zvířata; RNA ribozomální 16S; Salmonella enteritidis